2021
DOI: 10.3390/ma14112707
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Weld to S960MC High Strength Steel from Joining Process at Micro-Jet Cooling with Critical Parameters under Static and Fatigue Loading

Abstract: The paper is focused on testing the weld of the S960MC steel produced at the micro-jet cooling under static and fatigue loading at critical parameters. This kind of material was in the form of a sheet with a thickness equal to 2 mm. The joint was obtained using three different types of welding wires: EDFK 1000, Union NiMoCr and Union X96 at the same parameters of the process. The joints were examined using non-destructive and destructive tests. The results from non-destructive experiments enable us to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…They showed that a lower cooling rate leads to decreasing the yield point and tensile strength of S960 steel joints. Similar results were observed by Szymczak et al [32]. It was stated that micro-jet cooling, which increases the cooling rate, leads to improve the mechanical properties of welded joints.…”
Section: Introductionsupporting
confidence: 88%
“…They showed that a lower cooling rate leads to decreasing the yield point and tensile strength of S960 steel joints. Similar results were observed by Szymczak et al [32]. It was stated that micro-jet cooling, which increases the cooling rate, leads to improve the mechanical properties of welded joints.…”
Section: Introductionsupporting
confidence: 88%
“…This Special Issue, entitled “Development of Laser Welding and Surface Treatment of Metals”, is a complementary and valuable resource of knowledge in the following fields: Study of technological conditions of laser welding, investigation of test joints properties [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]; Analytical and numerical models of heat sources of laser beam and arc welding processes [ 19 , 20 , 22 , 23 ]; Study of laser cladding and investigations of the coating’s properties and tribological characteristics [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]; Study and development of fusion welding processes, investigation of properties of the deposit produced under forced cooling or underwater conditions [ 34 , 35 , 36 ]; Study of cladding, surfacing, and thermal spraying processes of wear-resistant coatings, characterization of the coatings [ 37 , 38 , 39 ]; Study of application of local strengthening of the thin-walled structure by laser treatment [ 40 ]. …”
Section: Short Characterization Of the Special Issuementioning
confidence: 99%
“…Study and development of fusion welding processes, investigation of properties of the deposit produced under forced cooling or underwater conditions [ 34 , 35 , 36 ];…”
Section: Short Characterization Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The fatigue test was supported by the requirements of the ASTM E468-18 standard [ 46 ] and employed the shape of the specimens and a value of the radius for the necking. This kind of hourglass specimen was elaborated on by one author of the article [ 47 , 48 ] in regards to application to the joints. The characteristic features of the specimen’s geometry are connected to a weld region, which directly occurs in the middle sections of the measuring zone.…”
Section: Details Of Weld Manufacturing Inspection and Testingmentioning
confidence: 99%